Can local adaptation research in plants inform selection of native plant materials? An analysis of experimental methodologies - Gibson, Alexis L; Espeland, Erin K; Wagner, Viktoria; Nelson, Cara R (Evolutionary applications, 2016)
Local adaptation is used as a criterion to select plant materials that will display high fitness in new environments. A large body of research has explored local adaptation in plants, however, to what extent findings can inform management decisions has not been formally evaluated. We assessed local adaptation literature for six key experimental methodologies that have the greatest effect on the application of research to selecting plant materials for natural resource management: experimental environment, response variables, maternal effects, intraspecific variation, selective agents, and spatial and temporal variability. We found that less than half of experiments used reciprocal transplants or natural field conditions, which are both informative for revegetation and restoration. Population growth rate was rarely (5%) assessed, and most studies measured only single generations (96%) and ran for less than a year. Emergence and establishment are limiting factors in successful revegetation and restoration, but the majority of studies measured later life-history stages (66%). Additionally, most studies included limited replication at the population and habitat levels and tested response to single abiotic selective factors (66%). Local adaptation research should be cautiously applied to management; future research could use alternative methodologies to allow managers to directly apply findings.
Keywords: experimental design; lifetime fitness; local adaptation; experimental methodology; plants; ecological experiments